2022
DOI: 10.1002/batt.202100361
|View full text |Cite
|
Sign up to set email alerts
|

Stability Enhancement of Zinc‐Ion Batteries Using Non‐Aqueous Electrolytes

Abstract: Owing to their high energy density and low cost, zinc‐ion batteries (ZIBs) are gaining much in popularity. However, in practice, issues with hydrogen evolution, zinc dendrite development, corrosion, and passivation persist. Such drawbacks prove difficult to eradicate completely. To address these difficulties, many techniques have been proposed including inhibitor addition, artificial SEI, and Zn electrode modification. As a result, some researchers believe that using non‐proton donor electrolytes or nonaqueous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(28 citation statements)
references
References 112 publications
(257 reference statements)
0
28
0
Order By: Relevance
“…[15,16] Unlike conventional electrolytes with solvated cations and anions through simple dissolving, the eutectic electrolytes contain complex anions and cations, which are formed through the strong interactions between the components. [17][18][19] For example, 2.0 M ZnCl 2 aqueous electrolyte contains solvated Zn ] + cations. [20] Compared with the traditional electrolytes, the eutectic electrolytes possess many characteristics, such as structural flexibility, good thermal/chemical stability, low vapor pressure, and wide potential windows.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[15,16] Unlike conventional electrolytes with solvated cations and anions through simple dissolving, the eutectic electrolytes contain complex anions and cations, which are formed through the strong interactions between the components. [17][18][19] For example, 2.0 M ZnCl 2 aqueous electrolyte contains solvated Zn ] + cations. [20] Compared with the traditional electrolytes, the eutectic electrolytes possess many characteristics, such as structural flexibility, good thermal/chemical stability, low vapor pressure, and wide potential windows.…”
Section: Introductionmentioning
confidence: 99%
“…When DESs is applied as the electrolyte for batteries, it is usually called eutectic electrolyte [15, 16] . Unlike conventional electrolytes with solvated cations and anions through simple dissolving, the eutectic electrolytes contain complex anions and cations, which are formed through the strong interactions between the components [17–19] . For example, 2.0 M ZnCl 2 aqueous electrolyte contains solvated Zn 2+ cations and Cl − anions, while AlCl 3 /acetamide (AcA) eutectic electrolyte has AlCl 4 − and Al 2 Cl 7 − anions and [AlCl 2 (AcA) 2 ] + cations [20] .…”
Section: Introductionmentioning
confidence: 99%
“…Rechargeable aqueous zinc battery with abundant zinc resources, cheap and readily available, high environmental stability, and aqueous electrolysis . The metal zinc anode not only has a relatively small electrode potential but also has a sufficiently high mass-specific capacity (820 mAh/g) and volume-specific capacity (5851 mAh/cm 3 ) . The cathode materials of aqueous zinc batteries are mainly Mn-based materials, V-based compounds, and Prussian blue compounds .…”
Section: Introductionmentioning
confidence: 99%
“…14 The metal zinc anode not only has a relatively small electrode potential but also has a sufficiently high mass-specific capacity (820 mAh/g) and volume-specific capacity (5851 mAh/cm 3 ). 15 The cathode materials of aqueous zinc batteries are mainly Mn-based materials, 16 V-based compounds, 17 and Prussian blue compounds. 18 Mn-based compounds have high discharge capacity and specific energy, but during the phase transition of zinc-ion intercalation, Mn 2+ dissolves during cycling, resulting in limited battery life.…”
Section: Introductionmentioning
confidence: 99%
“…[7,8] The behavior of Zn plating and stripping is sophisticated and can be modulated by several co-existing and interrelated factors, including the electrode configurations, [9][10][11] the charging/discharging protocols, [12] and the electrolyte formulations. [13][14][15][16][17] For example, it has been demonstrated that the anode morphology can affect the dendrite growth. By fabricating a Zn anode with a 3D sponge structure, the Ni-Zn cells could exhibit an improved cycle performance and a suppressed dendrite formation.…”
mentioning
confidence: 99%